The effects of blogging on pre-service teachers' reflective thinking and self-efficacy. Issue 2 (4th March 2021) - Cirak Kurt, Sevilay; Yildirim, Ibrahim
ABSTRACT: Although blogs have mostly been regarded to be useful in learning environments, it has been observed that few experimental studies with control groups have been conducted on the use of blogs in order to promote pre-service teachers' development. It is a mixed method research study conducted through pre-test and post-test experimental design with a control group. Although the research framework was based on the experimental quantitative data, qualitative interviews were also held with the experimental group at the end of the procedure. 46 pre-service teachers were included in the study, 21 for the experimental group, and 25 for the control group. In the end, qualitative data were collected from 14 voluntary pre-service teachers in the experimental group. As a result of the analyses, it was revealed that the experimental and control groups, which were identical at the beginning, differed significantly at the end of the experimental process in terms of reflective thinking and teacher self-efficacy. In other words, it was concluded that blogging was effective in developing the aforementioned variables, and the research findings were supported by qualitative interviews. Pre-service teachers in the experimental group pointed out that blogging contributed to the course, their professional and personal development.